Evaluation of Growth in Post-Mining Revegetation Land PT. Vale Indonesia Tbk. Sorowako, South Sulawesi - Yadi Setiadi; Adinda Adinda (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2013)
Reclamation and revegetation activities conducted by mining company to improve the function of land that has been affected by opening of the area is not easy. Evaluation of growth status is one of ways that can be used to overcome these obstacles. This study aimed to describe the status of growth of trees in the post-mining land and evaluate the causes of health problems on the growth of trees in the post-mining land. The method used in this study is using 4 pieces of plot objects made in two locations: in Harapan and in Inalahi. The parameters measured in identifying growth status are the plant’s diameter, plant’s height, growth performance, survival rate and soil samples. The species observed in this study is bitti (Vitex coffasus), johar (Senna siamea), kayu angin (Casuarina sp.), and sengon buto (Enterolobium macrocarpum).The results showed that johar has a value of 100% percent of individual growth, this means johar has a good life and adaptive at each observation plot. Percentage of the total of growing plants owned by sengon buto is 40% at the location of Harapan and johar is 30% in Inalahi location. Kayu angin at Harapan site and sengon buto at the location of Inalahi possess health value of 100%. It means that both plants resistant to health problems in their respective locations. Health problems occured is indicated by the presence of symptoms, such as, yellow leaves, black spots, and stagnation. The results of soil analysis on the observed plot indicates that low nutrient value in nitrogen (N), potassium (K), phosphorus (P) and calcium (Ca) to be one cause of the health problems in the plant.